Impacts of meteorology and emission reductions on haze pollution during the lockdown in the North China Plain - L. Liu; L. Liu; X. Long; Y. Li; Y. Li; Z. Zang; Z. Zang; F. Wang; Y. Han; Z. Bao; Y. Chen; T. Feng; et al. (Atmospheric Chemistry and Physics)
Haze events in the North China Plain (NCP) during the COVID-19 lockdown underscore the intricate challenges of air quality management amid reduced human activities. Utilizing the WRF-Chem model, we explored how sharp emission reductions and varying meteorological conditions influenced fine-particulate-matter (PM2.5) concentrations across the NCP. Our analysis highlights a marked regional contrast: in the northern NCP (NNCP), adverse meteorology largely offset emission reductions, resulting in PM2.5 increases of 30 to 60 µg m−3 during haze episodes. Conversely, the southern NCP (SNCP) benefited from favorable meteorological conditions that, combined with emission reductions, lowered PM2.5 by 20 to 40 µg m−3. These findings emphasize the critical role of meteorology in shaping the air quality response to emission changes, particularly in regions like the NNCP, where unfavorable weather patterns can counteract the benefits of emission reductions. Our study provides valuable insights into the complex interplay of emissions, meteorology, and pollutant dynamics, suggesting that adequate air quality strategies must integrate emission controls and meteorological considerations to address regional variations effectively.